Learning Beliefs, Time on Platform, and Academic Performance During the COVID-19 in University STEM Students - Lobos, Karla; Sáez-Delgado, Fabiola; Cobo-Rendón, Rubia; Mella Norambuena, Javier; Maldonado Trapp, Alejandra; Cisternas San Martín, Nataly; Bruna Jofré, Carola (Frontiers in Psychology, 2021)
Due to the closure of universities worldwide because of the COVID-19 pandemic, teaching methods were suddenly transformed to an emergency remote teaching (ERT) modality. Due to the practical nature of STEM courses, students cannot participate in activities in which manipulating objects is necessary for reaching the learning objectives. In this study, we analyze the relation among STEM students learning beliefs at the beginning of ERT (T1) with their Learning Management systems (LMS) time-on-task during the first semester of ERT and their final academic performance (T2). We used a prospective longitudinal design. Participants were 2063 students (32.3% females) from a university in Chile, where the academic year starts in March and finishes in December 2020. We assessed their learning and performance beliefs through an online questionnaire answered at the beginning of the academic semester (T1). Then, using learning analytics, we evaluated the amount of time invested in the CANVAS LMS and the academic performance achieved by students at the end of the academic semester (T2). The results show that students mainly stated negative beliefs about learning opportunities during ERT (n=1396; 67.7%). In addition, 48.5% (n=1000) of students stated beliefs of "medium" academic performance for the first semester (T1). Students with lower learning beliefs at T1 spent less time in the LMS during the semester and had a lower academic performance at T2 than students who had higher learning beliefs at T1. The implications of these findings on the role of teachers and institutions of higher education are discussed.